Gendered perceptions in maize supply chains: Evidence from Uganda - Van Campenhout, Bjorn; De, Anusha (International Food Policy Research Institute, 2021)
In situations with imperfect information, the way that value chain actors perceive each other is an important determinant of the value chain's structure and performance. Inaccurate perceptions may result in inefficient value chains, and systematic bias in perceptions may affect nclusiveness. In a case study on perceptions in Ugandan maize supply chains, a random sample of farmers were asked to rate upstream and downstream value chain actors-agro-input dealers, traders, and processors-on a set of important attributes that included ease of access, quality of services rendered, price competitiveness, and overall reputation. These value chain actors were then tracked and asked to assess themselves on the same set of attributes. We find that input dealers, traders, and processors assess themselves more favourably than farmers do. We also focus on heterogeneity in perceptions related to gender and find that for self- assessments, the gender of the value chain actor does not matter. However, the difference between how actors assess themselves and how farmers perceive them is larger for male than for female farmers, as female farmers appear to rate dealers, traders, and processors signicantly higher in several dimensions. The gender of the actor being rated does not affect the rating they receive, and gender-based homophily among women is not present in rating behaviour.